Hubungan Kausalitas antara Nilai Tukar, Produk Domestik Bruto dan Ekspor di Indonesia - Nurhaliza; Khairul Amri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This research aims to analyze the causal relationship between the exchange rate, GDP and exports both in the short and long term. The research target is time series data from exchange rate, GDP and Indonesian export variables. This research uses the Vector Error Correction Model (VECM) analysis method. The results of this research are that there is a unidirectional causal relationship between GDP and the exchange rate, and also between the exchange rate and exports. However, there is no causal relationship between exports and GDP, or vice versa. In the long term, the exchange rate has a significant negative impact on exports. Meanwhile, in the short term, exports have a negative and significant effect on the exchange rate and GDP. Apart from exports, GDP is also significantly influenced by the exchange.